Political Narratives and the US Partisan Gender Gap - Antinyan, Armenak; Bassetti, Thomas; Corazzini, Luca; Pavesi, Filippo (Frontiers in Psychology, 2021)
Social scientists have devoted considerable research effort to investigate the determinants of the Partisan Gender Gap (PGG), whereby US women (men) tend to exhibit more liberal (conservative) political preferences over time. Results of a survey experiment run during the COVID-19 emergency and involving 3,086 US residents show that exposing subjects to alternative narratives on the causes of the pandemic increases the PGG: relative to a baseline treatment in which no narrative manipulation is implemented, exposing subjects to either the Lab narrative (claiming that COVID-19 was caused by a lab accident in Wuhan) or the Nature narrative (according to which COVID-19 originated in the wildlife) makes women more liberal. The polarization effect documented in our experiment is magnified by the political orientation of participants' state of residence: the largest PGG effect is between men residing in Republican-leaning states and women living in Democratic-leaning states. JEL Classification: J16, D83, C83, C99, P16, D72.